Evaluation Study of Use of Interactive Multimedia 4.0-Based Teaching Materials - Mesterjon Mesterjon; Suwarni Suwarni; Dwi Rulismi; Sudarwan Danim (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
The evaluation carried out on the Utilization of Interactive Multimedia-Based Teaching Materials in student development courses is based on changes in "adaptation to the use of technology 4.0" which tend to change in trend, so this is inline with an interactive learning model, in encouraging student curiosity about knowledge, it becomes important to find out student strategies in using interactive learning media to improve the abilities of these students, the abilities intended include the abilities students use to communicate, both in the form of writing, speech, and the operation of technological devices and applications used. In an effort to reveal the facts from the findings when this research was conducted, the method used in this study was a quantitative method and data analysis techniques in this study the researchers used the CIPP model to evaluate the use of interactive multimedia-based teaching materials with 12 indicators and 53 questions related to utilization interactive multimedia-based teaching materials for early childhood students with an average score of 69%. Declared relevant and can be utilized in learning in early childhood. In its implementation, the samples from this study were tested on a limited scale and also tested on a large scale. For the limited-scale trial, it consisted of two parts of lecturers and one part of the student class, the number of which was randomly sampled, while for the large-scale test, it consisted of two parts of lecturers and two parts of student classes whose numbers were taken randomly. To support the required data iteration, in this study the implementation of collecting data used direct observation and oral tests. The data analysis technique applied uses the average score, percentage and t-test. It was concluded that the development of interactive multimedia-based teaching materials is feasible to use to improve language skills based on limited tests and broad tests. And the development model is effective in improving children's language skills significantly, seen in t_hitung > t_tabel.